2020
DOI: 10.3390/s20123577
|View full text |Cite
|
Sign up to set email alerts
|

Smoothness of Gait in Healthy and Cognitively Impaired Individuals: A Study on Italian Elderly Using Wearable Inertial Sensor

Abstract: The main purpose of the present study was to compare the smoothness of gait in older adults with and without cognitive impairments, using the harmonic ratio (HR), a metric derived from trunk accelerations. Ninety older adults aged over 65 (age: 78.9 ± 4.8 years; 62% female) underwent instrumental gait analysis, performed using a wearable inertial sensor and cognitive assessment with the Mini Mental State Examination (MMSE) and Addenbrooke’s Cognitive Examination Revised (ACE-R). They were stratified into three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…It is now notoriously known that mobility capacities also are worse in AD and MCI populations than age-matched cognitively unimpaired older adults. Overall, studies have reported slower gait speed, as well as a shorter and more variable stride [ 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 ]. Balance and postural control are also impaired [ 77 , 78 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 ], and kinematic studies investigating handwriting and finger-tapping movements have reported fine motor control deterioration in MCI and AD patients [ 96 , 97 , 98 , 99 , 100 ].…”
Section: Motor Function Studies In Pathological Aging: Alzheimer’smentioning
confidence: 99%
See 2 more Smart Citations
“…It is now notoriously known that mobility capacities also are worse in AD and MCI populations than age-matched cognitively unimpaired older adults. Overall, studies have reported slower gait speed, as well as a shorter and more variable stride [ 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 ]. Balance and postural control are also impaired [ 77 , 78 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 ], and kinematic studies investigating handwriting and finger-tapping movements have reported fine motor control deterioration in MCI and AD patients [ 96 , 97 , 98 , 99 , 100 ].…”
Section: Motor Function Studies In Pathological Aging: Alzheimer’smentioning
confidence: 99%
“…Studies have shown that modifications of sensorimotor functions may precede the onset of dementia [ 91 , 107 , 108 ] and that the presence of motor dysfunction could predict adverse outcomes in AD patients, such as fall risk [ 9 , 10 , 11 , 12 , 13 , 14 , 84 , 85 , 108 , 109 , 110 , 111 ]. In MCI, studies have also reported that motor function impairments are predictive of a higher risk of developing AD [ 79 , 98 , 108 , 112 ].…”
Section: Motor Function Studies In Pathological Aging: Alzheimer’smentioning
confidence: 99%
See 1 more Smart Citation
“…The HR is based on a spectral analysis of the acceleration signals and is related to the bilateral rhythmicity of movement, based on the measure of trunk acceleration during a stride that is expected to be formed by two alternating symmetric steps; it provides different kinds of information with respect to the traditional spatio-temporal parameters, which are focused on the lower limb symmetry at the distal level [ 22 ]. Recent studies demonstrated that the HR parameter is worthwhile in quantifying gait alterations associated with neurologic and orthopedic conditions, such as older people [ 23 ], Parkinson’s disease patients [ 22 ], multiple sclerosis [ 24 ], normal weight and obese children/adolescents [ 25 , 26 ], Prader–Willi patients [ 27 , 28 ], and cognitively impaired individuals [ 29 ]; in several cases, it is able to reveal subtle changes in gait that might occur well before they become detectable in terms of conventional spatio-temporal parameters [ 22 , 24 , 25 , 26 , 30 ]. Furthermore, it must be emphasized that trunk accelerations could be easily recorded by a single sensor in clinical settings or in other ecological contexts, without the limitations of a movement analysis laboratory, which requires expensive equipment, long setup times, and time-consuming post-processing procedures [ 26 , 28 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…The independent association of step-to-step symmetry with duration and frequency of walking may relate to typical deficits of older persons with CI, such as lower levels of PA performance [ 3 ] and a lower step-to-step symmetry [ 86 ], or the high association between step-to-step symmetry and walking balance [ 87 , 88 ], as a basic precondition of walking and thereby leading to a higher duration and frequency of walking.…”
Section: Discussionmentioning
confidence: 99%